The Dynamics and Strength of Linkages between the Stock Markets in the Czech Republic, Hungary and Poland after their EU Accession - Doman, Małgorzata; Doman, Ryszard (Dynamic Econometric Models, 2013)
We analyze the dynamics and strength of linkages between the Czech, Hungarian and Polish stock markets after the EU accession of the corresponding countries. In addition, we examine linkages between each of the markets and developed markets (European and US). The analysis is based on the daily quotations of the main representative stock indices (PX, BUX, WIG20, DAX, S&P 500) and includes the period from May 5, 2004 to July 20, 2012. The dynamics of dependencies is modeled by means of Markov-switching copula models, and the applied measures of the strength of the linkages are dynamic Spearman’s rho and tail dependence coefficients. The results show that dependencies between the considered emerging markets are very sensitive on market situation, but the linkages of these markets with the developed ones are stable.